Financial knowledge, financial management practices, financial pressure and financial stability among single female households in Malaysia - Lee, May Poh; Sabri, Mohamad Fazli (Malaysian Consumer and Family Economics Association, 2017)
Financial stability is recognised, conceptually important to the wellbeing of the households, but limited evidence is available on their predictors. Financial stability refers to a financially secure condition where individuals have the capacity to access financial resources for the aims to keep up a satisfactory way of life. A multi-stage random sampling was used to collect five hundred twenty one samples of female-headed households from six single mother associations divided by zones of East, North, South, West, Sabah and Sarawak of Malaysia. Thus, this study performed multiple linear regression to explore the determinants (financial pressure, financial knowledge and financial management practices) of financial stability. This current paper concluded the strongest predictive factor to the financial stability was financial management practices. Additionally, this study suggests that various respective bodies should corporate to organize some beneficial education programs in order to enhance households’ financial stability.